The Effect of Brand Asset Valuator on Usage Decision of Halodoc Application - Ghinda Nevithya Kono; Dedeh Fardiah; Kiki Zakiah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze the effect of the Brand Asset Valuator on the decision to use the Halodoc application. The dimensions Brand Asset Valuator studied include differentiation, relevance, esteem, and knowledge. The dimensions of usage decisions studied included product choice, brand choice, dealer choice, purchase amount, purchase time, and payment method. This type of research is quantitative research using simple random sampling of 123 respondents. The questionnaire used for data collection has been tested for validity and reliability. Data analysis performed included descriptive analysis, classical assumption test, multiple linear analysis, F test, T test, and coefficient of determination. The results of the F test analysis show that the dimensions of differentiation, relevance, esteem, and knowledge together influence the decision to use the Halodoc application. The results of the T test analysis show that the dimensions of differentiation, relevance, esteem, and knowledge partially affect the decision to use the Halodoc application.